Ignored works. (October 2021) - Bielsa, Esperança
This essay interrogates ignored works of art as a special kind of object that can shed some light on the nature of contemporary art worlds, as well as on wider social processes regarding our relationship with things and with our past. It provides a materialist perspective focused on discarded objects as an alternative to a mystifying view of the artworld that takes artistic autonomy for granted and obliterates the social conditions of creativity and success. Ignored works are normally outside the reach of art history and the sociology of art, yet the increasingly bigger realm of unrecognized and unvalued art provides, after the failure of the historical avant-garde, a space where critical autonomy can still develop. This essay attempts to illuminate this mostly invisible realm by relating it to other similar categories such as waste and forgetting. Finally, ignored works' connection to notions of authenticity is pointed out.